THE USE OF ROLE PLAY TO IMPROVE STUDENTS’ SPEAKING SKILL - Lisa Rakhmanina; Yuneva Yuneva (English Education Study Program Faculty of Teacher Training and Education, 2017)
ABSTRACT This study was aimed at: (1) 1) finding out how the use of role play in improving the students` English speaking ability; and (2) finding out whether or not the use of role play was able to improve the quality of Students` English speaking in Midwifery Major in Medical InstitutionBengkulu, Indonesia. This study applied Classroom Action Research with two cycles. The instruments used to find out the data were observation, tests and interview. The calculation of the study was applying simple calculation, i.e. by finding out the means differences of the pre-test and post-tests in Cycle 1 and Cycle 2. The study result showed that role play was applied during the process of the teaching and learning in the classroom. It showed significant different on students` English achievement from pre-test to post-test in Cycle 2. It means that role play method could improve students` English speaking skill and couldalso motivate students to learn more.